Petrographic and geochemical constraints on the formation of gravity‐defying speleothems - Adrian Immenhauser; Rene Hoffmann; Sylvia Riechelmann; Mathias Mueller; Dennis Scholz; Stefan Voigt; Stefan Niggemann; Dieter Buhl; Maximilian Dornseif; Alexander Platte (The Depositional Record, 2023)
Abstract Cave carbonates, seemingly growing in defiance of gravity, have attracted the community's interest for more than a century. This paper focusses on ‘helictites’, contorted vermiform speleothems with central capillaries. Petrographic, crystallographic and geochemical data of calcitic and aragonitic helictites (recent to 347 ka) from three caves in Western Germany are placed in context with previous work. Aragonitic helictites from one site, the Windloch Cave, form exceptionally large and complex structures that share similarities with the celebrated helictite arrays in the Asperge Cave in France. Aragonitic and calcitic helictites differ significantly in their crystal fabrics and internal geometry. Calcitic helictites are best described as a composite crystal fabric consisting of fibrous mesocrystals. Aragonite helictites display a complex fabric of acicular to platy crystals, some of which show evidence for growth‐twinning and perhaps crystallisation via a monoclinal precursor stage. The micro‐tomographic characterisation of several orders of channels and their complex architecture raises important questions regarding fluid migration and helictite architecture. In terms of their isotope geochemistry, helictites are depleted in 13C to various degrees, isotope values that are controlled by the mixing of fluids and mineralogy‐related fractionation. Regarding their δ18O values, most helictites overlap with other calcitic and aragonitic speleothems. Previous models explaining the twisted morphology of helictites are discussed from the viewpoint of fluid migration and CO2 degassing rates, mineralogy and helictite petrography. For the complex aragonitic helicities documented here, the most likely mechanisms to explain the contorted growth forms include the internal capillary network combined with localised (sector) growth at the helictite tip. The morphologically simpler calcitic helictites are best explained by capillary and surface flow. Future work should include geomicrobiology to assess the significance of induced mineralisation and transmission electron microscopy analysis to more quantitatively assign crystallographic properties.